Therapeutic Effects of a Traditional Chinese Medicine Formula Plus Tamoxifen vs. Tamoxifen for the Treatment of Mammary Gland Hyperplasia: A Meta-Analysis of Randomized Trials - Li, Hao-Tian; Liu, Hong-Hong; Yang, Yu-Xue; Wang, Tao; Zhou, Xue-Lin; Yu, Yang; Li, Su-Na; Zheng, Yi; Zhang, Ping; Wang, Rui-Lin; Li, Jian-Yu; Wei, Shi-Zhang; et al. (Frontiers in Pharmacology, 2018)
As a common disorder that accounts for over 70 % of all breast disease cases, mammary gland hyperplasia (MGH) causes a severe problem for the quality of patients' life, and confers an increased risk of breast carcinoma. However, the etiology and pathogenesis of MGH remain unclear, and the safety and efficacy of current western drug therapy for MGH still need to be improved. Therefore, a meta-analysis was conducted by our team to determine whether a TCM formula named Ru-Pi-Xiao in combination with tamoxifen or Ru-Pi-Xiao treated alone can show more prominent therapeutic effects against MGH with fewer adverse reactions than that of tamoxifen. Studies published before June 2017 were searched based on standardized searching rules in several mainstream medical databases. A total of 27 articles with 4,368 patients were enrolled in this meta-analysis. The results showed that the combination of Ru-Pi-Xiao and tamoxifen could exhibit better therapeutic effects against MGH than that of tamoxifen (OR: 3.79; 95% CI: 3.09-4.65; P < 0.00001) with a lower incidence of adverse reactions (OR: 0.35; 95% CI: 0.28 to 0.43; P < 0.00001). The results also suggested that this combination could improve the level of progesterone (MD: 2.22; 95% CI: 1.72 to 2.71; P < 0.00001) and decrease the size of breast lump (MD: -0.67; 95% CI: -0.86 to -0.49; P < 0.00001) to a greater extent, which might provide a possible explanation for the pharmacodynamic mechanism of Ru-Pi-Xiao plus tamoxifen. In conclusion, Ru-Pi-Xiao and related preparations could be recommended as auxiliary therapy combined tamoxifen for the treatment of MGH.